若丨ab-2丨+(b-1)的平方=0,求1/ab+1/(a+1) (b+1)+1/(a+2) (b+2)+…+1/(a+2009) (b+2009)的值
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 10:50:52
若丨ab-2丨+(b-1)的平方=0,求1/ab+1/(a+1) (b+1)+1/(a+2) (b+2)+…+1/(a+2009) (b+2009)的值
若丨ab-2丨+(b-1)的平方=0,求1/ab+1/(a+1) (b+1)+1/(a+2) (b+2)+…+1/(a+2009) (b+2009)的值
若丨ab-2丨+(b-1)的平方=0,求1/ab+1/(a+1) (b+1)+1/(a+2) (b+2)+…+1/(a+2009) (b+2009)的值
|ab-2|+(b-1)²=0
∴ab-2=0
b-1=0
∴a=2
b=1
∴1/ab+1/(a+1)(b+1)+1/(a+2)(b+2)+……+1/(a+2009)(b+2009)
=1/1×2+1/2×3+1/3×4+1/4×5+……+1/2010×2011
=1-1/2+1/2-1/3+1/3-1/4+1/4-1/5+……+1/2010-1/2011
=1-1/2011
=2010/2011
若丨ab-2丨+(b-1)的平方=0,则ab-2=0,b-1=0,解得a=2,b=1
1/ab+1/(a+1) (b+1)+1/(a+2) (b+2)+…+1/(a+2009) (b+2009)
=1/1*2+1/2*3+。。。+1/2010*2011
=1-1/2+1/2-1/3+。。。+1/2010-1/2011
=2010/2011
丨ab-2丨+(b-1)的平方=0
所以 ab-2=0,b-1=0
所以b=1,a=2/b=2
所以原式=1/1×2+1/2×3……+1/2010×2011
=1-1/2+1/2-1/3+……+1/2010-1/2011
=1-1/2011
=2010/2011
易知b=1,a=2(两个非负数之和为零,则必都为零)
则所求为1/2+1/(2*3)+1/(3*4)+。。。+1/(2010*2011)
拆开为 1/2+(1/2-1/3)+(1/3-1/4)+。。。+(1/2010-1/2011)
中间消去得1-1/2011=2010/2011